Synopsis: Macroeconomic factor influence on agricultural program sustainability in Kaduna state, Nigeria - Hatzenbuehler, Patrick L.; Mavrotas, George (International Food Policy Research Institute, 2017)
In this study, we measure the degree to which changes in key macroeconomic variables – global oil prices or donor funding levels – affect the fiscal conditions of the Kaduna Ministry of Agriculture and Forestry (KDMAF), and, thus, the likelihood of the Kaduna government to sustain agricultural programs following a fiscal shock.